In Vitro Whole Blood Clot Lysis for Fibrinolytic Activity Study Using D-Dimer and Confocal Microscopy - Abuzar Elnager; Wan Zaidah Abdullah; Rosline Hassan; Zamzuri Idris; Nadiah Wan Arfah; S. A. Sulaiman; Zulkifli Mustafa (Advances in Hematology)
This study aimed to evaluate in vitro whole blood (WB) clot lysis method for the assessment of fibrinolytic activity. Standardized unresected (uncut) retracted WB clot was incubated in pool platelet poor plasma (PPP) for varying incubation times and in streptokinase (SK) at different concentrations. The fibrinolytic activity was assessed by D-dimer (DD), confocal microscopy, and clot weight. DD was measured photometrically by immunoturbidimetric method. There was a significant difference in mean DD levels according to SK concentrations (P=0.007). The mean DD±SD according to the SK concentrations of 5, 30, 50, and 100 IU/mL was: 0.69±0.12, 0.78±0.14, 1.04±0.14 and 2.40±1.09 μg/mL. There were no significant changes of clot weight at different SK concentrations. Gradual loss and increased branching of fibrin in both PPP and SK were observed. Quantitation of DD and morphology of fibrin loss as observed by the imaging features are in keeping with fibrinolytic activity. Combination of DD levels and confocal microscopic features was successfully applied to evaluate the in vitro WB clot lysis method described here.